Late-onset preeclampsia and eclampsia - Santos, Vitorino Modesto (Revista de Medicina e Saúde de Brasília, 2017)
The author comments three articles about late-onset peeclampsia and eclamplsia, emphasizing the main features on the clinical manifestations and prevention. Moreover the role of hypertensive disorders of pregnancy is highlighted aiming to increase the awareness of primary care workes.